Reproductive performance of laying snails (Archachatina marginata) fed on roughages and different concentrate mixes - Jimoh, Olatunji Abubakar (2021)
The result revealed snails fed with UPWP had the least final weight and weight gain which was accompanied by the highest feed intake across the treatments. Average egg laid, hatchability, fertility, embryo mortality, and average juvenile produced by snails on roughage-based diet were significantly the least across the treatments. High gonadosomatic index of snails on leaf meal-based diet accompanied with better reproductive output in laying snails was recorded.